Analysis of synonymous codon usage patterns in the edible fungus Volvariella volvacea. (15th December 2016) - Jiang, Wei; Lv, Beibei; Wu, Xiao; Wang, Jinbin; Wu, Guogan; Shi, Chunhui; Tang, Xueming
Abstract: In this study, trends in synonymous codons usage of Volvariella volvecea have been first examined by analysis of complete coding sequences and gene chip data. The results showed that GC content at three codon positions are obviously different and there were several factors shaping the codon usage of V. volvacea genes, including base composition. The comparison of codon usage among four edible fungi such as V. volvacea, Agaricus bisporus, Coprinopsis cinerea, and Pleurotus ostreatus indicated that the similar codon usage pattern was used among V. volvacea, A. bisporus and P. ostreatus, but there was significantly different codon usage pattern of C. cinerea . Two arrays of optimal codons were determined by effective number of codons (ENC) values and gene chip database separately, resulting that most of the ENC‐predicted optimal codons were included in the array of gene chip resulted optimal codons. This study can provide useful information for codon usage pattern analysis and gene transformation of V. volvacea .